Chloride modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
Through the preparation method of chloride-modified lithium-rich manganese-based positive electrode material, spray drying and calcining methods, the problems of complex preparation process and large energy consumption in the prior art are solved, and the material performance is significantly improved and the process is simplified.
Patent Information
- Application Number
- CN202510021250.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the preparation process of lithium-rich manganese-based cathode materials is complex, has a large energy consumption, and the performance of the obtained material is not significantly improved.
The preparation method of lithium-rich manganese-based positive electrode material modified by chloride is used to prepare lithium-rich manganese-based positive electrode material by spray drying and calcining. Sodium chloride, potassium chloride or lithium chloride are used as chloride modifiers, which simplifies the process flow and reduces energy consumption.
The electronic conductivity of the material is improved, the specific capacity of the first discharge and the efficiency of the first Coulomb are significantly improved, and the capacity retention rate under long cycles reaches more than 80%, simplifying the process and reducing energy consumption.
Smart Images

Figure CN119797446A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a preparation method of a chloride-modified lithium-rich manganese-based positive electrode material and application thereof. Background Art
[0002] Lithium-ion batteries occupy a dominant position in various electrochemical energy storage devices due to their high energy density, low self-discharge, long cycle life and environmental friendliness. They are also the main power source for portable electronic products and new energy vehicles.
[0003] The cathode material is one of the key factors affecting the performance of lithium-ion batteries and is also the key to improving energy density. Compared with the currently commercialized cathode materials, lithium-rich manganese-based cathode materials have higher energy density (>250mAh g -1 ), higher operating voltage (about 3.6V) and other advantages, making it a very promising new generation of positive electrode material.
[0004] However, lithium-rich manganese-based positive electrode materials also have inherent problems, such as low initial charge and discharge efficiency and large capacity loss, which restrict the pace of commercialization. Secondly, lithium-rich manganese-based materials synthesized by different methods differ in microstructure and other aspects, and their electrochemical properties will also be affected. In addition, the difficulty and complexity of industrial operations in material production will also affect actual production applications. Invention patent CN113871589B discloses the use of potassium chloride and other materials to assist in modification, so that the cycle life of lithium-rich manganese-based positive electrode materials is improved; but due to the introduction of potassium chloride during the calcination process, the calcined material needs to be washed, filtered, and dried to remove impurities, the operation process is complicated, and energy consumption is increased; invention patent CN119008924A discloses the use of sol-gel method to prepare materials, the preparation method is simple and environmentally friendly, but the performance of the resulting material is not significantly improved. Summary of the invention
[0005] The present invention provides a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, so as to solve the problems of the prior art that the operation process is complicated, the energy consumption is large, and the performance improvement of the obtained material is not obvious.
[0006] In order to achieve the above object, the technical solution of the present invention is: a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0007] Step 1: According to the chemical formula Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 stoichiometric ratio, lithium acetate, nickel acetate, manganese acetate, cobalt acetate and chloride salt were dissolved in deionized water, and citric acid monohydrate was added as a complexing agent;
[0008] Step 2: preparing the mixed solution by spray drying to obtain a lithium-rich manganese-based positive electrode material precursor powder;
[0009] Step 3: calcine the precursor powder in a muffle furnace in an air or oxygen atmosphere to obtain a lithium-rich manganese-based positive electrode material powder.
[0010] Furthermore, the above-mentioned chloride salt is sodium chloride, potassium chloride or lithium chloride, and the added amount accounts for 8-50% of the total mass of the metal source.
[0011] Furthermore, in the above step 1, the total concentration of metal ions in the mixed solution is 0.15-2.0 mol / L, and the concentration of citric acid is 0.1-0.5 mol / L.
[0012] Furthermore, in the above step 1, the stirring speed during solution mixing is 300-600 rpm / min, the stirring time is 1-4h, and the stirring temperature is 20-40°C.
[0013] Furthermore, in the above step 2, the temperatures of the air inlet and outlet during the spray drying process are 200-250°C and 100-130°C respectively, the peristaltic pump peristaltic speed is 10-20rpm, and the preheating evaporation temperature is 120-300°C.
[0014] Furthermore, in the above step three, the temperature rise rate of the precursor powder calcined in the muffle furnace is 2-3-5°C / min, and the calcination temperature reaches 800-1100°C and then calcined for 0.3-10h. The calcination atmosphere is air or oxygen, and the powder is naturally cooled to room temperature after calcination.
[0015] Furthermore, the lithium-rich manganese-based positive electrode material prepared by the above preparation method.
[0016] Furthermore, the above lithium-rich manganese-based positive electrode material is used in lithium-ion batteries.
[0017] Compared with the prior art, the advantages of the present invention are:
[0018] 1. The lithium-rich manganese-based material prepared by the preparation method of the present invention is characterized by SEM and other tests, which show that a small amount of metal ions are in-situ doped on the surface of the material, which improves the electronic conductivity of the material, improves the first discharge specific capacity, and has a high first coulombic efficiency; and the preparation method can make the surface of the material coated with a spinel structure to improve the cycle performance. The button battery finally prepared can reach 301mAh / g at the first discharge at 0.1C, the first coulombic efficiency is 84.97%, and the capacity retention rate after 400 cycles at 1C reaches more than 80%.
[0019] 2. The method of the present invention combines the molten salt method and the spray method, and the prepared material does not need to increase energy consumption like the molten salt method alone. Compared with preparation methods such as sol-gel, the preparation process is relatively simple. Compared with other preparation methods that add chlorides such as potassium chloride and lithium chloride, the prepared lithium-rich manganese-based positive electrode material does not have excess chloride salt residue after characterization testing, so there is no need for separation and purification steps, which can reduce energy consumption, and the production process cycle is short, which is conducive to practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a comparison diagram of X-ray diffraction curves (XRD) of Comparative Example 1, Example 1, and Example 2;
[0021] Figure 2 It is a comparison diagram of X-ray diffraction curves (XRD) of Comparative Example 1, Example 3, and Example 4;
[0022] Figure 3 The scanning electron microscope (SEM) images of Comparative Example 1, Example 1 and Example 2 are shown;
[0023] Figure 4 The scanning electron microscope (SEM) images of Comparative Example 1, Example 3 and Example 4 are shown;
[0024] Figure 5 The selected area SEM image and element distribution diagram of Comparative Example 1;
[0025] Figure 6 The selected area SEM image and element distribution diagram of Example 3;
[0026] Figure 7 The first charge and discharge curves of Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 at 0.1C are shown;
[0027] Figure 8 This is a performance comparison chart of Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 after 400 cycles at 1C;
[0028] Fig. 9 X-ray photoelectron spectroscopy (XPS) diagrams of Comparative Example 1, Example 3, and Example 4;
[0029] Fig.10 These are the Hall effect diagrams of Comparative Example 1, Example 3, and Example 4. DETAILED DESCRIPTION
[0030] The preparation method of the present invention is further described below by specific examples. It should be understood by those skilled in the art that the examples are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] Embodiment 1, a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0032] Step 1: According to the chemical formula Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 stoichiometric ratio, lithium acetate, nickel acetate, manganese acetate, cobalt acetate and potassium chloride were dissolved in deionized water, mixed at 40°C for 2h, and the stirring speed of the solution was 400rpm / min to obtain a lithium-rich manganese-based precursor mixed solution;
[0033] The total metal ion concentration is 0.15 mol / L, wherein the lithium is in excess of 3% to compensate for the lithium loss during the high-temperature sintering process; the mass of the potassium chloride is 8% of the total metal mass; and the concentration of citric acid monohydrate as a complexing agent is 0.3 mol / L.
[0034] Step 2: The lithium-rich manganese-based precursor mixed solution obtained in step 1 is connected to a spray dryer to obtain a lithium-rich manganese-based precursor by spray drying. The air inlet temperature of the spray dryer is controlled at 230-250°C, the outlet air temperature is controlled at 110°C, the peristaltic pump peristaltic speed is 15rpm, and the preheating evaporation temperature is 220°C.
[0035] Step 3: Place the precursor material obtained in step 2 in a muffle furnace, heat it up at a rate of 5°C / min, heat it to 1000°C and calcine it for 20 minutes. The calcination process is carried out in an air atmosphere, and air is continuously supplied to the muffle furnace by a blower. After cooling naturally to room temperature, grind the product into powder to obtain a lithium-rich manganese-based positive electrode material.
[0036] Embodiment 2, a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0037] Step 1: Dissolve lithium acetate, nickel acetate, manganese acetate, cobalt acetate and sodium chloride in deionized water according to the stoichiometric ratio of the chemical formula Li1.2Ni0.13Co0.13Mn0.54O2, mix at 40°C for 2h, and stir the solution at a speed of 400rpm / min to obtain a lithium-rich manganese-based precursor mixed solution;
[0038] The total metal ion concentration is 0.15 mol / L, wherein the lithium is in excess of 3% to compensate for lithium loss during high-temperature sintering; the mass of the sodium chloride is 50% of the total metal mass; and the concentration of citric acid monohydrate as a complexing agent is 0.3 mol / L.
[0039] Step 2: The lithium-rich manganese-based precursor mixed solution obtained in step 1 is connected to a spray dryer to obtain a lithium-rich manganese-based precursor by spray drying. The air inlet temperature of the spray dryer is controlled at 230-250°C, the outlet air temperature is controlled at 110°C, the peristaltic pump peristaltic speed is 15rpm, and the preheating evaporation temperature is 220°C.
[0040] Step 3: Place the precursor material obtained in step 2 in a muffle furnace, heat it up at a rate of 5°C / min, heat it to 1000°C and calcine it for 20 minutes. The calcination process is carried out in an air atmosphere, and air is continuously supplied to the muffle furnace by a blower. After naturally cooling to room temperature, grind the product into powder to obtain the lithium-rich manganese-based positive electrode material prepared by the preparation method.
[0041] Example 3, a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, comprises the following steps: The difference from Example 2 is that the mass of sodium chloride added in step 1 is 25%, the calcination temperature in step 3 is 900°C, and the calcination time is 5h.
[0042] Embodiment 4 is different from Embodiment 3 in that the mass of sodium chloride added as chloride salt in step 1 is 16.7%.
[0043] Comparative Example 1 provides a method for preparing a chloride-modified lithium-rich manganese-based positive electrode material. The preparation method is the same as Example 1 except that potassium chloride is not added in step 1.
[0044] The above-mentioned comparative example 1 and embodiments 1-4 were added to a ball mill with a conductive agent SuperP in a mass ratio of 8:1, and wet-milled with ethanol. The ball milling speed was 450rpm / min, the ball-to-material ratio was 100:1, and the ball milling time was 8h. The wet-milled sample was dried in a blast drying oven at 80°C for 10h to obtain a composite material of lithium-rich manganese-based active material and conductive agent. The composite material was then slurried with a CMC binder, and after coating, drying, and cutting, it was used as a positive electrode. The positive electrode and the counter electrode lithium sheet were assembled into a lithium-ion button half-cell, and different test parameters were set to explore the electrochemical properties of the prepared positive electrode material.
[0045] like Figure 1 and Figure 2 As shown in the X-ray diffraction curve, Examples 1, 2, 3, and 4 are all typical lithium-rich manganese structures, without any new impurity phases, and can correspond well to the α-NaFeO2 layered structure. The diffraction peaks at 20-24° correspond well to the superstructure of the C2 / m phase in the lithium-rich manganese material. The lattice parameter of Example 3 is enlarged, showing obvious characteristic peaks of the spinel phase. Figure 3 and Figure 4The SEM test results were further analyzed for morphology and elements. The particle size of the material samples of Comparative Example 1 and Examples 1-4 was uniformly distributed, and there was no significant change in size, which was about 200-500nm. There was no significant change in particle morphology between Examples 1-4 and Comparative Example 1. From the particle element distribution diagram of Comparative Example 1 and Example 3 ( Figure 5 and Figure 6 ) It can be seen that the Mn, Ni, and Co elements are evenly distributed on the surface of the material in Comparative Example 1. Example 3 is a material prepared by adding sodium chloride. The EDS element distribution results show that the Mn, Ni, and Co elements on the surface are also evenly distributed. In addition, the material obtained by this preparation method has no Cl element residue on the surface, and a small amount of metallic Na element exists. From the 0.1C first charge and discharge curve Figure 7 It can be seen that compared with the first discharge capacity of 269 mAh / g in comparative example 1, the first discharge capacity of Examples 1-4 at 0.1C (C = 200 mAh / g) is improved. Compared with the first coulombic efficiency of 76.12% in comparative example 1, the first coulombic efficiency of most of Examples 1-4 prepared by the preparation method proposed in this patent is improved. Among them, the first discharge capacity of Example 3 is as high as 301 mAh / g, which is about 40 mAh / g higher than the first discharge capacity of comparative example 1, and its first coulombic efficiency is also greatly improved to 84.97%. From the 400 long cycle diagram at 1C ( Figure 8 ) It can be seen that the capacity retention rate of comparative example 1 is 56.44%, while the cycle performance of the embodiments is greatly improved, among which the capacity retention rate of embodiment 2 is 81.21%, and the capacity retention rate of embodiment 3 is 72.03%. Figure 7 and Figure 8 The data are summarized in Table 1. It can be seen that under the conditions of room temperature 30°C and voltage range 2.0-4.8V, the modified Examples 1-4 significantly improve the first discharge specific capacity of the positive electrode material, the first cycle coulomb efficiency is improved, and at the same time have better long cycle performance.
[0046] Table 1 Characteristic parameters of electrochemical performance in comparative examples and embodiments
[0047]
[0048] Pass XPS test ( Fig. 9 ), it can be seen that there is Na in Example 3 and Example 4 + Compared with Comparative Example 1, the presence of metal ions Mn 4+ / Mn 3+ , Ni 3+ / Ni 2+ and Co 3+ / Co 4+ The proportion has changed significantly. Fig.10The electronic conductivity and carrier mobility of Comparative Example 1, Example 3, and Example 4 are compared. It can be seen from the figure that the electronic conductivity and carrier concentration of Example 3 and Example 4 are significantly improved, and the electronic conductivity of Example 3 and Example 4 is maintained at 10 -5 S / cm order of magnitude, while Comparative Example 1 maintained at 10 -6 S / cm, and the carrier mobility of Example 3 is about 700cm 2 / Vs, which is greatly improved compared with that of comparative example 1. Therefore, chloride greatly improves the electronic conductivity of the lithium-rich positive electrode material, thereby increasing the charge transfer rate in the electrochemical reaction.
[0049] Among the above embodiments, Embodiment 3 is the best embodiment.
[0050] In summary, the lithium-rich manganese-based positive electrode material prepared by the method of the present invention has a high initial discharge specific capacity, a high initial charge and discharge efficiency, and a good capacity retention rate under long cycles.
[0051] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a chloride-modified lithium-rich manganese-based positive electrode material, characterized in that: The specific steps include: Step 1: According to the chemical formula Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 stoichiometric ratio, lithium acetate, nickel acetate, manganese acetate, cobalt acetate and chloride salt were dissolved in deionized water, and citric acid monohydrate was added as a complexing agent; Step 2: preparing the mixed solution by spray drying to obtain a lithium-rich manganese-based positive electrode material precursor powder; Step 3: calcine the precursor powder in a muffle furnace in an air or oxygen atmosphere to obtain a lithium-rich manganese-based positive electrode material powder.
2. The method for preparing a chloride-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The chloride salt is sodium chloride, potassium chloride or lithium chloride, and the added amount accounts for 8-50% of the total mass of the metal source.
3. The method for preparing a chloride-modified lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: In the step 1, the total concentration of metal ions in the mixed solution is 0.15-2.0 mol / L, and the concentration of citric acid is 0.1-0.5 mol / L.
4. The method for preparing a chloride-modified lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: In the step 1, the stirring speed during solution mixing is 300-600 rpm / min, the stirring time is 1-4 h, and the stirring temperature is 20-40°C.
5. The method for preparing a chloride-modified lithium-rich manganese-based positive electrode material according to claim 4, characterized in that: In the step 2, the temperatures of the air inlet and outlet during the spray drying process are 200-250°C and 100-130°C respectively, the peristaltic pump peristaltic speed is 10-20rpm, and the preheating evaporation temperature is 120-300°C.
6. The method for preparing a chloride-modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: In the step 3, the temperature rise rate of the precursor powder in the muffle furnace is 2-3-5°C / min, and the calcination temperature reaches 800-1100°C and then calcined for 0.3-10h. The calcination atmosphere is air, and the powder is naturally cooled to room temperature after calcination.
7. The lithium-rich manganese-based positive electrode material obtained by the preparation method according to claim 1.
8. Use of the lithium-rich manganese-based positive electrode material according to claim 1 in lithium-ion batteries.
Citation Information
Patent Citations
Lithium ion battery lithium-rich manganese-based positive electrode material and spray drying preparation method thereof
CN108878862A
Modified lithium-rich manganese-based oxide positive electrode material and preparation method thereof
CN110797527A
Chloride ion doped modified lithium-rich layered anode material and preparation method thereof
CN111463427A
Lithium-rich manganese-based positive electrode material, preparation method, battery positive electrode and battery
CN117300141A
Silicon dioxide coated silver nanowire modified lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN118281187A